Respuesta :
(4•4-3•1-3•3)\[0-(-2)•(-2)]
complete the parenthesis first
(4•4-3•1-3•3)
complete the multiply and divided first from left to right
16 -3-9 =
then complete the subtraction
13-9 =4
now
[0-(-2)•(-2)]
complete the parenthesis first
do the multiplication
-2*-2
4
now subtract
0-4=-4
so we have
-4/4
Answer: -1
Use PEMDAS
P Parentheses first
E Exponents (ie Powers and Square Roots, etc.)
MD Multiplication and Division (left-to-right)
AS Addition and Subtraction (left-to-right)
[tex]\dfrac{4\cdot4-3\cdot1-3\cdot3}{0-(-2)\cdot(-2)}=\dfrac{16-3-9}{-4}=\dfrac{4}{-4}=-1[/tex]